Trends in marginal lung allograft survival: Advanced‐age donors improve. Issue 9 (21st July 2022) - Miggins, John James; Reul, Ross Michael; Loor, Gabriel; Ferreira, Liam D.; Garcha, Puneet S.; Goss, John A.; Rana, Abbas A.
Abstract: Introduction: Although lung demand continues to outpace supply, 75% of potential donor lungs are discarded without being transplanted in the United States. To identify the discarded cohorts best suited to alleviate the lung shortage and reduce waitlist mortality, we explored changes in survival over time for five marginal donor definitions: age >60 years, smoking history >20 pack‐years, PaO2 /FiO2 < 300 mmHg, purulent bronchoscopic secretions, and chest radiograph infiltrates. Methods: Our retrospective cohort study separated 27 803 lung recipients in the UNOS Database into three 5‐year eras by transplant date: 2005–2009, 2010–2014, and 2015–2019. Multivariable Cox proportional hazards regression and Kaplan‐Meier analysis with log‐rank test were used to compare survival across the eras. Results: Three definitions—low PaO2 /FiO2, purulent bronchoscopic secretions, and abnormal chest radiographs—did not bear out as truly marginal, demonstrating lack of significantly elevated risk. Advanced donor age demonstrated considerable survival improvement (HR (95% CI): 1.47 (1.26–1.72) in 2005–2009 down to 1.14 (.97–1.35) for 2015–2019), with protective factors being recipients <60 years, moderate recipient BMI, and low Lung Allocation Score (LAS). Donors with smoking history failed to demonstrate any significant improvement (HR (95% CI): 1.09 (1.01–1.17) in 2005–2009 increasing to 1.22 (1.08–1.38) in 2015–2019). Conclusions: Advanced donor age, previously the most significant risk factor, has improved to near‐benchmark levels, demonstrating the possibility for matching older donors to healthier non‐elderly recipients in selected circumstances. Low PaO2 /FiO2, bronchoscopic secretions, and abnormal radiographs demonstrated survival on par with standard donors. Significant donor smoking history, a moderate risk factor, has failed to improve.